Inhibition of the NLRP3 inflammasome improves lifespan in animal murine model of Hutchinson–Gilford Progeria. Issue 10 (27th August 2021) - González‐Dominguez, Alvaro; Montañez, Raúl; Castejón‐Vega, Beatriz; Nuñez‐Vasco, Jéssica; Lendines‐Cordero, Débora; Wang, Chun; Mbalaviele, Gabriel; Navarro‐Pando, José M; Alcocer‐Gómez, Elísabet; Cordero, Mario D
Abstract: Inflammation is a hallmark of aging and accelerated aging syndromes such as Hutchinson–Gilford progeria syndrome (HGPS). In this study, we present evidence of increased expression of the components of the NLRP3 inflammasome pathway in HGPS skin fibroblasts, an outcome that was associated with morphological changes of the nuclei of the cells. Lymphoblasts from HGPS patients also showed increased basal levels of NLRP3 and caspase 1. Consistent with these results, the expression of caspase 1 and Nlrp3, but not of the other inflammasome receptors was higher in the heart and liver of Zmpste24 −/− mice, which phenocopy the human disease. These data were further corroborated in Lmna G609G/G609G mice, another HGPS animal model. We also showed that pharmacological inhibition of the NLRP3 inflammasome by its selective inhibitor, MCC950, improved cellular phenotype, significantly extended the lifespan of progeroid animals, and reduced inflammasome‐dependent inflammation. These findings suggest that inhibition of the NLRP3 inflammasome is a potential therapeutic approach for the treatment of HGPS. SYNOPSIS: This study reveals a critical role of the NLRP3‐inflammasome complex in the pathogenesis of Hutchinson‐Gilford Progeria (HGPS). Targeting NLRP3 may be a novel potential therapeutic strategy for progeria treatment. NLRP3 signalling is hyperactivated in the skin fibroblasts and lymphoblast of HPGS patients and animal models. Inhibition of NLRP3 ameliorates phenotype of skin fibroblasts from patients and improves survival and bodyweight of animal models. Inhibition of NLRP3 suppresses the inflammasome‐dependent inflammation in animal models. Abstract : This study reveals a critical role of the NLRP3‐inflammasome complex in the pathogenesis of Hutchinson‐Gilford Progeria (HGPS). Targeting NLRP3 may be a novel potential therapeutic strategy for progeria treatment.